Регіональна волинська преса і громадська думка в 1989–1991 роках (за матеріалами обласних газет «Радянська Волинь» та «Молодий ленінець») - Теребус, Оксана Леонідівна; Terebus, Oksana L. (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті зроблено спробу проаналізувати роль і місце волинських регіональних газет «Радянська Волинь» та «Молодий ленінець» у формуванні громадської думки жителів області в період 1989–1991 років. Розглянуто тематику та проблематику матеріалів, поданих в газетах, які стосувалися політичного та суспільного життя краю. Автор звернув увагу на особливості висвітлення тих чи інших тем журналістами видань.

This paper attempts to analyze the role and place of Volyn regional newspapers “RadianskaVolyn” and “MolodyiLeninets”in the formation of public opinion of residents of the area during the 1989-1991s. Themes and issues concerning the political and social life of the region and presented in the newspapers have been considered.The author draws attention to the features of coveringcertain topics by journalists, as well as drawing attention to the elements of objectivity and subjectivity in way of information presentation. The author has analyzed a lot of columns, in which newspapers editorspublished readers’ letters andtheir comments on social and important events. Publications enable trackingordered materials, i.e. the ones, the content of whicheditors do not approve .Moreover, based on the materials presented as letters from readers (People's Movement, Ukraine, role and place of aparty in the society,history of Ukraine, public organizations, symbols,etc), there arises the conclusion that the public cares about the future of the country.
Volyn Regional Newspapers and Public Opinion in1989–1991 (on the materials of regional newspapers “RadianskaVolyn” and “MolodyiLeninets”)
Keywords: обласні газети; рубрики; журналісти; мітинги; громадська думка; regional newspapers; columns; journalists; meetings; public opinion